Twin-screw extrusion scales down for pharma and nanotech - Martin, Charlie (Knovel, 2011)
"As a more advanced alternative to batch mixing, HSEI machines are enabling pharma users to create sophisticated new dosage forms by compounding active pharmaceutical ingredients with polymers. In the nanotechnology world, HSEI twin-screw extruders incorporate functional nanoparticles into the next generation of aerospace, electronics, and packaging materials."--Description from Knovel site.
Keywords: Plastics -- Extrusion.; Pharmaceutical technology.; elektronické knihy; electronic books